Anticonvulsive and neuroprotective effects of synergetic combination of phenytoin and gastrodin on the convulsion induced by penicillin in mice. (15th June 2015) - Zhou, Ziqi; Lin, Yanzhu; Zheng, Hongyi; He, Yuzhong; Xu, Haohua; Zhang, Siheng; Weng, Wen; Li, Wei; Zhu, Linyan; Yang, Haifeng
Abstract Phenytoin (PHT) is a commonly prescribed first‐line antiepileptic drug. However, long‐term administration of PHT can cause memory loss and balance disturbance. Gastrodin (GD) is the major bioactive component in Tianma and has sedative, anticonvulsive, memory strengthening, and neuroprotective effects. To combine the two drugs seems attractive; however, little was known about the efficacy of combination therapy. In this study, convulsive attack was successfully induced by penicillin. Isobolographic analysis, memory and balance behavior test, histopathological examination, and Western blot analysis were used to investigate whether the combination therapy of GD and PHT can enhance anticonvulsive effect and reduce the side effects associated with PHT. The GD alone (950.60 mg/kg) and the PHT alone (45.50 mg/kg) could produce an anticonvulsive effect, while comparable effect could be produced by PHT : GD = 1 : 50 (8.59 : 429.27 mg/kg), which reduce the dose of PHT by 81% and GD by 55%. After the chronic anticonvulsive experiments of 16 days, the balance disturbance and short‐/long‐term memory loss were observed in the PHT group, while the PHT + GD therapy can protect the normal balance and memory function. The neuron morphology of hippocampus was preserved, and the number of surviving neurons after combination therapy was more than the model group. The amount of NF‐κB (p65) expression was increased in combination group. All above suggested the potential of the combination of PHT and GD enhances the anticonvulsive effect and the neuroprotective effect and reduces the PHT‐associated memory and balance disturbance. The PHT + GD strategy would provide new possibilities as a novel promising methodology to treat epileptic patients.